Prosecuting environmental harm before the International Criminal Court / Matthew Gillett, University of Essex. - Gillett, Matthew, 1979- (Studies on international courts and tribunals., 2022)
The threat of anthropocentric environmental harm grows more pressing each year. Around the world, human activities are devastating the natural environment and contributing to potentially irreversible climate change. This book explores the ways in which the International Criminal Court may effectively prosecute those who cause or contribute to serious environmental destruction. Written by an international lawyer who has prosecuted cases of war crimes, crimes against humanity, and genocide, it provides insights into the procedures, laws, and techniques capable of leading to convictions against those who harm the environment.